Genetic control of meiosis surveillance mechanisms in mammals - Huang, Yan; Roig, Ignasi (Frontiers in Cell and Developmental Biology, 2023)
Meiosis is a specialized cell division that generates haploid gametes and is critical for successful sexual reproduction. During the extended meiotic prophase I, homologous chromosomes progressively pair, synapse and desynapse. These chromosomal dynamics are tightly integrated with meiotic recombination (MR), during which programmed DNA double-strand breaks (DSBs) are formed and subsequently repaired. Consequently, parental chromosome arms reciprocally exchange, ultimately ensuring accurate homolog segregation and genetic diversity in the offspring. Surveillance mechanisms carefully monitor the MR and homologous chromosome synapsis during meiotic prophase I to avoid producing aberrant chromosomes and defective gametes. Errors in these critical processes would lead to aneuploidy and/or genetic instability. Studies of mutation in mouse models, coupled with advances in genomic technologies, lead us to more clearly understand how meiosis is controlled and how meiotic errors are linked to mammalian infertility. Here, we review the genetic regulations of these major meiotic events in mice and highlight our current understanding of their surveillance mechanisms. Furthermore, we summarize meiotic prophase genes, the mutations that activate the surveillance system leading to meiotic prophase arrest in mouse models, and their corresponding genetic variants identified in human infertile patients. Finally, we discuss their value for the diagnosis of causes of meiosis-based infertility in humans.